Action plan 1984, Volume 1 - Bauchi State Agricultural Development Programme (Bauchi: Bauchi State Agricultural Development Programme, 1984)
This volume is divided into 2 main sections: overall plans by activity and activities by Development Area
Volume 1
osc 04/04/2019
Arch
Keywords: Economic planning; Agricultural development; Bauchi, Nigeria